Social Media Branding Strategy to Increase the Tourist Attraction of the Palintang Rock Cliffs, Wargaluyu Village - Pertiwi, Dwi Endah; Fazri, Muhamad Hafidz Sohibul; Fahrulia, Dhita; Uljayanti, Icharuly; Alviandi, Raphael; Rohmah, Nuroh Tuhfatur; Misbahudin, Misbahudin; Zulfany, Neng Sri; Hadi, Asparul; Aziz, Ujang Abdul; Firmansyah, Herdi; Sobari, Ari Abdi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Cadas Palintang Cliff at Wargaluyu village has great natural potential and high value as a tourist destination. Although its popularity among tourists is still limited. This journal aims to strategise branding through the use of social media in an effort to increase interest in tourism at Cadas Palintang Cliff. USing quantitative approach, this journal analises branding strategies which focuses on destination image management, content creation, along with the usage of social media platforms like Instagram, Facebook, and YouTube. Data is collected through deep interviews with tourism management, social media content analyzer, and direct observation. Study shows that consistent and interesting branding, combined with active interaction on social media, can increase tourist’s interest and broaden the market. Usage of local hashtags, collaboration with influencers, along with visual content which highlights the beautiful nature of Cadas Palintang Cliff became a key element in this strategy. This journal suggests recommendations to tourist’s destination management in optimizing social media to promote tourist’s destination sustainably.